2010
DOI: 10.2176/nmc.50.257
|View full text |Cite
|
Sign up to set email alerts
|

Direct Relief of Levodopa-Induced Dyskinesia by Stimulation in the Area Above the Subthalamic Nucleus in a Patient With Parkinson's Disease -Case Report-

Abstract: A 71-year-old woman with a 25-year history of levodopa (LD)-responsive Parkinson's disease (PD) developed on-off motor fluctuation and severe peak dose dyskinesia. She underwent deep brain stimulation of the subthalamic nucleus (STN-DBS). STN-DBS induced attenuation of her cardinal PD symptoms and marked improvement of dyskinesia without reduction of LD dosage perioperatively. STN-DBS thus markedly attenuated the cardinal symptoms of PD. LD-induced dyskinesia can also be controlled via reduction of LD dosage a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…First, most studies suggested that stimulating pallidothalamic, pallidosubthalamic, or subthalamopallidal fibers, which are densely distributed above the STN, can cause effects similar to those of thalamic or pallidal DBS. 8 24 25 26 In particular, the lenticular fasciculus, which lies between the STN inferiorly and the zona incerta superiorly, is a white matter tract from the dorsal globus pallidus interna (GPi). This tract transverses the internal capsule and then combines with the ansa lenticularis (the ventral GPi outflow tracts) to form the thalamic fasciculus in the field H1 of Forel, which then terminates at the ventroanterior/ventrolateral (VA/VL) thalamic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…First, most studies suggested that stimulating pallidothalamic, pallidosubthalamic, or subthalamopallidal fibers, which are densely distributed above the STN, can cause effects similar to those of thalamic or pallidal DBS. 8 24 25 26 In particular, the lenticular fasciculus, which lies between the STN inferiorly and the zona incerta superiorly, is a white matter tract from the dorsal globus pallidus interna (GPi). This tract transverses the internal capsule and then combines with the ansa lenticularis (the ventral GPi outflow tracts) to form the thalamic fasciculus in the field H1 of Forel, which then terminates at the ventroanterior/ventrolateral (VA/VL) thalamic nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Most results obtained in patients undergoing subthalamic stimulation conclude that the reduction of dyskinesias is due to the reduction of L-DOPA administration [13]. On the other hand, a few studies suggest that STN stimulation per se has an antidyskinetic effect [14][16] while still others claim it exacerbates dyskinesia [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Luego de transcurridos 5 años de la toma de la medicación antes mencionada, se comienzan a presentar fluctuaciones de la movilidad, cada vez menos controlables y se presentan efectos adversos tales como freezing, el fenómeno de wearing off, disquinesias relacionadas a la levodopa, entre otros; por lo tanto, se llega a un punto en el que se hace necesario el empleo de la intervención quirúrgica para modular lo que previamente era controlado con medicamentos. 1,5,9 Se conocen varias técnicas quirúrgicas para el tratamiento de la EP avanzada. Entre las que más destacan se incluye la estimulación del núcleo subtalámico, la cual posee un costo exagerado y la subtalamotomía en un sólo blanco por radiofrecuencia, pero que, por temor a la producción del hemibalismo postoperatorio, fueron realizadas en pocos grupos quirúrgicos en el mundo.…”
Section: Discussionunclassified
“…En los últimos años, las técnicas quirúrgicas para la EP se han ido modificando, siendo ya conocida la estimulación del núcleo subtalámico del cerebro, realizada por Benabid en el año de 1995, pero que lamentablemente carece de acogida por su alto costo, abandono del paciente y difícil accesibilidad. 1,[3][4][5] Las ventajas de esta técnica incluyen su carácter mínimamente invasivo, el empleo de anestesia local, el estado vigil del paciente durante la operación para que pueda ejecutar actos motores más o menos complejos con sus extremidades y dialogar con los cirujanos; permitiendo así, orientar la delimitación exacta del área a intervenir, unido a la comprobación neurofisiológica por semi-micro-registros de la actividad eléctrica cerebral.…”
Section: Introductionunclassified